2013
DOI: 10.1002/bse.1822
|View full text |Cite
|
Sign up to set email alerts
|

Distinctive Features of Environmental Innovators: An Econometric Analysis

Abstract: This paper analyzes the main determinants influencing environmental innovators (i.e. firms developing or adopting environmental innovations) in Spain with respect to non-environmental innovators. Similarly to other contributions in the literature, our results show that Spanish environmental innovators respond to regulatory stimulus in the form of demand-pull and technology-push instruments. They have a high internal technological capability and combine internal and external information sources, mostly in coope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
90
1
6

Year Published

2014
2014
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(108 citation statements)
references
References 72 publications
5
90
1
6
Order By: Relevance
“…Using the Flash Eurobarometer survey 315 [22] as their main source of data, this paper finds that even though Romania is significantly under the EU average when it comes to eco-innovation adoption, there is an increasing interest on eco-innovative activities, due to the changes in demand towards green products/services both in multinationals or SMEs. Del Rio et al [23] analyse the main determinants influencing SMEs' environmental innovators compared to general innovators in Spain, as it has a weaker green innovation system than in other European countries (e.g., Germany). Using annual data obtained from the Spanish Technological Innovation Panel database (PITEC) 2009, and similarly to other countries, results show that Spanish environmental innovators respond to demand-pull and technology push factors, mainly in high-polluting sectors.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Using the Flash Eurobarometer survey 315 [22] as their main source of data, this paper finds that even though Romania is significantly under the EU average when it comes to eco-innovation adoption, there is an increasing interest on eco-innovative activities, due to the changes in demand towards green products/services both in multinationals or SMEs. Del Rio et al [23] analyse the main determinants influencing SMEs' environmental innovators compared to general innovators in Spain, as it has a weaker green innovation system than in other European countries (e.g., Germany). Using annual data obtained from the Spanish Technological Innovation Panel database (PITEC) 2009, and similarly to other countries, results show that Spanish environmental innovators respond to demand-pull and technology push factors, mainly in high-polluting sectors.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, empirical studies have shown inconsistent results. This holds for studies investigating (stricter) regulations and the creation and adoption of environmental innovations by firms [82,83], but also with regard to R&D subsidies [84]. With regard to government support (e.g., from business development corporations, local authorities, job centres and the state government), Lejprcas et al could only confirm a positive effect on innovative and financial performance for less-innovative firms [50].…”
Section: Political Support (Government)mentioning
confidence: 99%
“…Although many of the determinants of environmental innovation are expected to be similar to those of general innovation (Rennings, 2000;Del Río, 2009), the empirical literature has in fact identified quite distinctive features in the case of ecoinnovation (Hojnik and Ruzzier, 2015;Del Río et al, 2016). Specifically, and as a result of this double externality problem, regulation makes eco-innovation different (Del Río et al, 2015).…”
Section: Introductionmentioning
confidence: 99%